Organoleptic Analysis of Temitel (Tempeh Mix Egg) as an Alternative Processed Protein Source - Halawa, Elfredo J; Ruqaya Junus; Irza N Ranti; Meildy E Pascoal; Cheren Kuhu; Romiza Arika (HM Publisher, 2024)
The high need for animal protein in Indonesia has not been met optimally. Tempeh, as a source of vegetable protein, has great potential but is less popular with some groups because of its monotonous taste. Temitel, a mixture of tempeh and eggs, is presented as an alternative processed protein source which is expected to increase protein consumption in the community. This research aims to analyze the organoleptics of Temitel as a basis for developing tempeh-based functional food products. This study used a completely randomized design (CRD) with three treatments (tempeh:egg proportions) and three replications. Organoleptic parameters observed include color, aroma, texture and taste. Data were analyzed using the ANOVA test and Duncan's advanced test. The results showed that the proportion of tempe:egg had a significant effect on the organoleptic parameters of Temitel. Temitel with a higher proportion of tempeh has a darker color, stronger tempeh aroma and taste, and a denser texture. Temitel with a higher proportion of eggs has a brighter color, stronger egg aroma and taste, and a softer texture. Temitel is an alternative processed protein source that has great potential for development. The tempeh:egg proportion can be adjusted to produce Temitel with organoleptic characteristics that suit consumer preferences. Temitel is expected to increase protein consumption in society, especially among those who don't like tempeh.